Needlestick injuries at Kimberley Hospital Complex - Loots, Johanna Jacoba Maria (My University, 2012)
Needlestick Injuries (NSI) that occur at Kimberley Hospital Complex (KHC) are reported by various categories of staff ranging from general workers to managers. They are regarded as medico-legal events and are classified as specific adverse events (AE). An AE is defined as any unexpected, unintended, unwanted event or circumstance that could have or did lead to unintended or unexpected harm, loss or damage. Although there were regular meetings related to NSI, there has been no systematic analysis of applicable data related to employees at KHC. The aim of this study was therefore to describe the NSI at KHC over a 1 year period (1 Jan 2009 – 31 Dec 2009) in order to obtain baseline information which will contribute towards improved planning of targeted preventive strategies in this setting. Methodology: A descriptive cross-sectional study was undertaken. This involved a retrospective review of selected hospital records relating to NSI reported by employees during this study period. No primary data was collected. Results: A total of 32 employees reported NSI during the study period. The prevalence of NSI was 2% of overall staff compliment. The highest reported prevalence was amongst the doctors (13, 10.4%) and the lowest amongst the general assistants (5, 0.6%). The majority of NSIs occurred during the recapping activity (20, 62.5%), was reported by female employees (27, 84.4%), took place mainly during normal working hours (23, 72%), and were mostly located within the Internal Medicine Department (10, 31.3%). About a third of the employees who reported NSIs were between 26 to 35 years (31%). The total treatment costs including drugs and vaccines provided during the study period were R 13 509.12, and the total laboratory test costs were R20 978.24. Overall the costs for drugs, vaccines and laboratory tests that made up the post-exposure measures amounted to R34 487.36. Results from this study suggest that reporting of NSI and other adverse events involving employees should be handled separately from those of patients. It is also important to profile the diverse employees that maybe at risk for this specific exposure and ensure that they are provided with the necessary training in this regard. There is a need to strengthen the relationship between the Quality Assurance Unit and the Wellness Clinic in order to optimize utilization of data regarding reported NSIs. Strategies to prevent NSIs should consider training on a regular basis and supervisors should work more closely with safety representatives in preventing NSIs.
M.P.H., Faculty of Health Science, University of the Witwatersrand, 2011
Keywords: Wounds and Injuries; Hospital Personnel